A deliberate resurrection of matter : a transhumanist vision (Postmodern Science; the Deathly Grammar of word and Consciousness) - Gebhardt, Hartwin (Department of English Language and Literature, 2016)
Section 1 will be a mostly descriptive engagement with the concept of 'post modern science', and will thus both quote and interpret scientific debate extensively. Although 'chaos' has been constituted as a formal discipline only after the publication of Gravity's Rainbow (GR), it has been included in the overview of postmodern science since it has both direct and indirect bearing on issues included within the scope of the thesis. Section 2 will deal with the use of postmodern science, and the 'scientific discourse' in general, within philosophical and artistic / literary activity. Special attention will be given to both limits and implications of this use. Section 2 will also develop the link with GR and Pynchcon's metaphorical use of the scientific discourse. Section 3 will deal more specifically with GR and will analyze various themes and topics in the light of the preceding discussion in Sections 1 and 2. Section 4 will focus on the broader connotations of GR and on possible avenues of 'escape' from cultural, economic, political and, even more elementary, linguistic processes and systems, in both definition and oppression of (and via) 'self.